P28 Mortality, ethnicity and nativity in England and Wales-do we see a healthy migrant effect?. (13th September 2016) - Wohland, P; Norman, P; Rees, P
Abstract : Background: Population diversity in England and Wales (E&W) has steadily increased since 1991; the proportion of people defining themselves as not White has since doubled and increased to 14% of the total population by 2011. However, unlike other immigration countries mortality for ethnic groups, an important population health indicator, is not collected. To fill this knowledge gap we previously developed methods to estimate mortality for ethnic groups, one of which is using information of the geographical distribution of groups. We found that life expectancies (LE) for many ethnic minorities were below those of the White British. LE for ethnic minorities were related to the degree of deprivation groups experienced and partly counter-acted by the recency of arrival. Over time, the number of second and subsequent generation migrants who still define themselves with their parents' ethnic group has increased. Here we investigate mortality differences between ethnic groups by nativity, to explore further the impact of nativity on health. Methods: We estimated mortality for ethnic groups in E&W by nativity- born in the UK and born abroad- for 18 groups as defined in the census 2011. Mortality rates are estimated using Rees et. al . (2009) geographically weighted method. The derived mortality rates are used in standard abridged lifetable methodology to compute LE. Results: Briefly, variation in LE at birth for women is not very large but the differences between groups are in many instances significant. For LE at birth we find the highest LE for Arab women born abroad with 83.5 years and the lowest in Pakistani women born in the UK (82.2 years). Between women born in the UK, the maximum difference in LE is just over one year, for women born abroad the difference is nearly 1.3 years. In general we observe that the population born abroad has a higher LE at birth compared to the population born in the UK, but only in the White British group this difference is significant. Conclusion: We find a general trend in all ethnic groups that first generation migrants have better health compared to subsequent generations. However, due to small numbers, only 13% of the population in E&W is born abroad, variations are mostly not significant. Even though variation between groups estimated here are small, they are significant. These result iterate the importance to collect actual ethnic mortality data, to allow us to finally research the real variation in ethnic mortality in E&W.